Liquidity, interest rates and house prices in the Euro area: a DSGE analysis - Rubio, Margarita; Carrasco-Gallego, José A. (Emerald, 2016)
In this paper, we propose a two-country monetary union DSGE model with housing, in order to study how different shocks contributed to the increase in housing prices and credit in the EMU prior to the crisis. One of the countries is calibrated to represent the core group in the Euro area while the other one corresponds to the periphery. First, we explore how a liquidity shock (or a decrease in the interest rate) affects house prices and the real economy through the asset price and the collateral channel. Then, we analyze how a house price shock in the periphery and a technology shock in the core countries are transmitted to the both economies. We find that a combination of an increase in liquidity in the Euro area coming from the common monetary policy, together with asymmetric house price and technology shocks, can explain the increase in house prices in the Euro area and the stronger credit growth in the peripheral economies in the pre-crisis period.